Differences in blood pressure before and after administration of local anesthetic among obese adult female patients - Ahyar Riza; Indra B. Siregardew; Abdullah Oes; Tilagamalar Tilagamalar (Journal of Dentomaxillofacial Science, 2021)
Objective: To determine the differences in blood pressure of female patients aged 26-45 years with normal Body Mass Index (BMI) and obesity after administration of local anesthetic containing adrenaline before dental extraction in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, Universitas Sumatera Utara.Material and Methods: This was an experimental study with a single group pretest-posttest design. Simple random sampling was used to select the subjects. 32 female patients aged 26-45 years participated in this study. 16 female patients with normal BMI and 16 female patients with obesity visited the clinic for dental extraction in the Department of Oral and Maxillofacial Surgery, Faculty of Dentistry, University of North Sumatera. Blood pressure of each subject was measured before and after administration of anesthesia. Data obtained was statistically analyzed using Dependent T-test.Results: Systolic blood pressure between normal and obese subjects after administration of local anesthetic with adrenaline 1:80000 showed significant differences (p<0.05). Diastolic blood pressure between normal and obese subjects after administration of local anesthetic with adrenaline 1:80000 showed no significant differences (p>0.05).Conclusion: Administration of local anesthetic with adrenaline 1: 80000 can increase the blood pressure in obese patients and patients with normal BMI. Obese subjects are more prone to higher diastolic and systolic blood pressure changes compared to subjects with normal BMI.